ANALYSIS OF INFLUENCE OF TARIFF OF IMPORT DUTY, EXCHANGE RATE, IMPORT VALUE AND IMPORT VOLUME ON INCOME OF IMPORT DUTY IN INDONESIA WITH FREE TRADE AGREEMENT (FTA) AS MODERATING VARIABLE - Sinaga, Meiwanro Sinaga (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objectives of the research examines and analyze the influence of tariff of import duty, exchange rate, import value and import volume on the revenue of import duty and Free Trade Agreement (FTA) as moderating variabel. The type of this research was causality research. The population were total revenue of import duty, tariff of import duty, exchange rate, import value and import volume per three months in 2003-2005 obtained from main Office of Directorate General of Customs and Excise on Directorate of Revenue and Strategic Plan of Directorate General of Customs and Excise also from the official site of Central Bureau of Statistics. This research used census method. This research used secondary data. The data were analyzed by using multiple linear regression analysis and residual test. The results of the research showed that the tariff of import duty, exchange rate of Rupiah to US Dollar, import value and import volume simultaneously had significant influence on the revenue of import duty. Partially import value and import volume had significant influence on the revenue of import duty. Free Trade Agreement (FTA) cannot moderate the correlation between the tariff of import duty, exchange rate of Rupiah to US Dollar, import value and import volume on the revenue of import duty in Indonesia.